Genotype-Phenotype Correlations in Autosomal Dominant Osteogenesis Imperfecta - I. Mouna Ben Amor; Francis H. Glorieux; Frank Rauch (Journal of Osteoporosis)
Osteogenesis imperfecta, discussed in Baldridge et al. 2008 is an inherited bone fragility disorder with a wide range of clinical severity that in the majority of cases is caused by mutations in COL1A1 or COL1A2, the genes that encode the two collagen type I alpha chains. Here we describe genotype-phenotype correlations in OI patients who have mutations affecting collagen type I. This paper is based on findings in a large single-centre OI population and a review of the literature.